2016
DOI: 10.1186/s40545-016-0091-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing medication packaging and labelling appropriateness in Sri Lanka

Abstract: BackgroundThere is substantial evidence of poor dispensing practices with inadequate packaging and labelling of medicines, and limited advice on their usage in low and middle-income countries (LMICs). We examined the labelling and packaging of medicines identified during a survey of 1322 households in six regions of Sri Lanka between 2010 and 2013 conducted using the World Health Organization (WHO) methodology for household surveys. We compared medicines obtained from public and private sources and asked inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…It is also important to note that, a patient’s ability to read a simulated dispensing label may not be completely indicative of the readability and comprehensibility of their own medications labels [ 20 ]. Among the few reported, is a considerably large study conducted by Athuruliya et al , [ 21 ] where completeness and understandability of dosing instructions given with dispensing labels were assessed in a house-hold survey. However, understandability of dosing instructions were assessed as a simple yes/no question without using objective criteria which the authors highlight as a limitation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to note that, a patient’s ability to read a simulated dispensing label may not be completely indicative of the readability and comprehensibility of their own medications labels [ 20 ]. Among the few reported, is a considerably large study conducted by Athuruliya et al , [ 21 ] where completeness and understandability of dosing instructions given with dispensing labels were assessed in a house-hold survey. However, understandability of dosing instructions were assessed as a simple yes/no question without using objective criteria which the authors highlight as a limitation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the few reported, is a considerably large study conducted by Athuruliya et al , [ 21 ] where completeness and understandability of dosing instructions given with dispensing labels were assessed in a house-hold survey. However, understandability of dosing instructions were assessed as a simple yes/no question without using objective criteria which the authors highlight as a limitation [ 21 ]. Unaka et al, [ 12 ] assessed written instructions provided at discharge by a hospital medication service but the study was limited to paediatric medication charts.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, labeling “swallow tablet as a whole without breaking or cursing” on controlled released tablets and “tablets should be chewed before swallowing” on chewable tablets are needed to ensure that patients use it in the intended manner. Studies in SriLanka [ 6 ] and Malaysia [ 7 ] have also reported insufficient labeling of dispensed medicines as required by the regulatory authorities. The study done in SriLanka used WHO manual for household survey, and included both Western and traditional medicine but did not evaluate repackaging by family members and their understanding of medication administration instruction [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in SriLanka [ 6 ] and Malaysia [ 7 ] have also reported insufficient labeling of dispensed medicines as required by the regulatory authorities. The study done in SriLanka used WHO manual for household survey, and included both Western and traditional medicine but did not evaluate repackaging by family members and their understanding of medication administration instruction [ 6 ]. Similarly, study in Malaysia used simulated client method to explore labeling requirement of dispensed medicine using a case of common cold but limits itself to single simulated case, observer bias and being a pilot study [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation